Pola Asuh Orang Tua Tunggal Dalam Pendidikan Akhlak Anak di MI Ma’arif Surotrunan Alian - Nurohmah, Wiwit Mina; Murtopo, Bahrun Ali (Tarbi: Jurnal Ilmiah Mahasiswa, 2026)
This study aims to determine: 1) What type of parenting style is applied by single parents at MI Ma'arif Surotrunan Alian. 2) What are the moral traits of students raised by single parents in terms of honesty, politeness, and responsibility at MI Ma'arif Surotrunan Alian in the Academic Year 2022/2023. 3) What are the obstacles faced by single parents in educating their children's morals at MI Ma'arif Surotrunan Alian. In this study, the author used a qualitative method, where data collection was not guided by theory, but based on the discovery of facts during the field research. The data collection techniques employed were observation, interviews, and documentation. The data analysis technique used was the Miles and Huberman model, which consists of three stages: 1) Data Reduction, 2) Data Display, and 3) Conclusion Drawing. The results of the research conducted by the author on Single Parenting Patterns in Children's Moral Education at MI Ma'arif Surotrunan Alian can be summarized as follows: Among five single parents, four of them adopted a democratic parenting style, while one adopted a neglectful parenting style. Moreover, single parents at MI Ma'arif Surotrunan Alian were found to be quite successful in educating their children's morals, particularly in instilling values of honesty, politeness, and responsibility related to academic performance. However, the process of guiding and nurturing their children's morals did not go smoothly for all five single parents, and they faced various challenges, including limited knowledge of religious teachings, their own education level, limited time with their children, lack of support from the other parent, and economic factors.